Original research: factors related to persistent amblyopia after surgical correction in unilateral congenital blepharoptosis - Yi-Hua Chen; Pei-Wei Huang; Yueh-Ju Tsai (BMC Ophthalmology)
Abstract Background Managing unilateral congenital blepharoptosis is challenging, because it is difficult to ensure symmetry under general anesthesia, and some children suffer from persistent amblyopia even after surgical correction. This study aimed to evaluate the risk factors associated with persistent amblyopia and to develop a risk stratification score for predicting persistent amblyopia in children who underwent surgical correction for unilateral congenital blepharoptosis. Methods This retrospective cohort study consecutively included 226 patients under the age of 12 years who underwent surgical correction for unilateral congenital blepharoptosis at Linkou Chang Gung Memorial Hospital between January 1, 2006, and December 31, 2022. Patients who still had amblyopia in the ptotic eye after individualized amblyopia treatment and ptosis surgery, with at least one year of follow-up, were classified as the persistent amblyopia group. All others were classified as the non-amblyopia group. Data collected included demographic information, age at surgery, surgical method, presence of strabismus, refraction errors, baseline amblyopia, and visual outcomes. These variables were compared between the two groups and used to predict persistent amblyopia. Results Among the 226 eyes studied, persistent amblyopia was observed in 58 eyes (25.7%) after at least one year of follow-up. Factors significantly associated with persistent amblyopia included age at surgery (under 36 months or over 72 months) (p = 0.004), presence of strabismus (p = 0.001), baseline amblyopia (p < 0.001), and higher baseline astigmatism (p = 0.004). Risk stratification scores based on these variables indicated that patients in the high-risk group had a prevalence of persistent amblyopia of 61%, compared to 42% in the intermediate-risk group and only 6% in the low-risk group. Conclusions Persistent amblyopia in children with unilateral congenital blepharoptosis is influenced by multiple factors including age at surgery, presence of strabismus, baseline amblyopia, and astigmatism. Identifying these risk factors can help in stratifying high risk patients and guiding preventative recommendations. Trial registration The present study was approved by the Institutional Review Board of Chang Gung Memorial Hospital (IRB No.: 202402306B0) and was conducted in accordance with the Declaration of Helsinki.